Deposition of au, au-v and au-vox on si wafers by co-sputtering technique - Narksitipan S. (2014)
Au, Au-V and Au-VOx thin films were deposited on Si wafers by a co-sputtering technique. A fourpoint probe shows that the electrical resistivity of pure Au thin film on Si wafer without annealing is 7.2 m ·cm. The resistivities of thin films deposited on Si wafers, with or without annealing, tended to increase with the increase in the V and VOx concentrations, and were attributable to the inhibited drift mobility of charge carriers within the films. By using the nanoindentation technique, the hardness in all cases also tended to increase with the increase in the V and VOx concentrations. The hardness of pure Au, without annealing, was 2.52 GPa. It decreased to 1.80 GPa and 1.75 GPa after annealing at 200 °C and 400 °C, respectively. SEM and TEM analyses revealed the presence of nanosized particles on the surfaces of the thin films. XRD analysis of Au-4.00% VOx film deposited on Si wafer detected the presence of Au, VO and Si. However, SAED analysis only detected the presence of Au on the film.